Local Postsynaptic Signaling on Slow Time Scales in Reciprocal Olfactory Bulb Granule Cell Spines Matches Asynchronous Release - Ona Jodar, Tiffany; Lage-Rupprecht, Vanessa; Abraham, Nixon M.; Rose, Christine R.; Egger, Veronica (Frontiers in Synaptic Neuroscience, 2020)
In the vertebrate olfactory bulb (OB), axonless granule cells (GC) mediate self- and lateral inhibitory interactions between mitral/tufted cells via reciprocal dendrodendritic synapses. Locally triggered release of GABA from the large reciprocal GC spines occurs on both fast and slow time scales, possibly enabling parallel processing during olfactory perception. Here we investigate local mechanisms for asynchronous spine output. To reveal the temporal and spatial characteristics of postsynaptic ion transients, we imaged spine and adjacent dendrite Ca2+- and Na+-signals with minimal exogenous buffering by the respective fluorescent indicator dyes upon two-photon uncaging of DNI-glutamate in OB slices from juvenile rats. Both postsynaptic fluorescence signals decayed slowly, with average half durations in the spine head of t1/2_∆[Ca2+]i ∼500 ms and t1/2_∆[Na+]i ∼1000 ms. We also analysed the kinetics of already existing data of postsynaptic spine Ca2+-signals in response to glomerular stimulation in OB slices from adult mice, either WT or animals with partial GC glutamate receptor deletions (NMDAR: GluN1 subunit; AMPAR: GluA2 subunit). In a large subset of spines the fluorescence signal had a protracted rise time (average time to peak ∼400 ms, range 20 ms - >1000 ms). This slow rise was independent of Ca2+ entry via NMDARs, since similarly slow signals occurred in ∆GluN1 GCs. Additional Ca2+ entry in ∆GluA2 GCs (with AMPARs rendered Ca2+-permeable), however, resulted in larger ∆F/Fs that rose yet more slowly. Thus GC spines appear to dispose of several local mechanisms to promote asynchronous GABA release, which are reflected in the time course of recurrent inhibition.